Electrolyte requirements and supplementation in exercising horses - Bergero, Domenico; Valle, E (MTT, 2008)
Nowadays it is necessary to have a multidisciplinary approach to the horse, to find the key for the optimal performance not only by considering macronutrients such as protein, fat and sugar, but also minerals, like electrolytes. The electrolytes include minerals, such as sodium (Na), potassium (K) chloride (Cl), calcium (Ca) and magnesium (Mg), that when dissolving in a appropriate solvent are ionized and conduct an electric current. In the body ions are dissolved in three main compartments: the fluid within the cells, the fluid in the space surrounding the cells, and the blood. They affect many metabolic processes such as the passage of fluid between and within cells (osmosis), the function of the neuromuscular system, the acid-base balance and pH, and the thermoregulatory process. The body maintains the optimal concentration of electrolytes in each compartment by moving electrolytes into or out of the cells. They are very important for the organisms because there is a continuing loss from the body and there are no body stores of electrolytes other than those carried in the gastrointestinal tract. This review analyses the main characteristics of the most important electrolytes for horses with particular emphasis to sodium, potassium and chloride. Also calcium and magnesium, even if they are generally considered for its pivotal role in the bone metabolism, are considered as electrolytes present in plasma and extracellular fluids.
Keywords: Ko; electrolytes; horse; sweat; acid base balance; requirements